Impact of Social Support on Suicidal Ideation and Attempts Among Gender Minority Adults. (January 2023) - Pate, Ashley R.; DeShong, Hilary L.; Stafford, Ty W.D.; Nadorff, Michael R.
This study examined the impact of social support from family, non-gender minority friends, gender minority friends, and religious groups on suicidal ideation, suicide attempt history, and the number of suicide attempts. Researchers hypothesized that these types of social support were associated with lower suicidal thoughts and behaviors. This research is a secondary analysis of the Virginia Transgender Health Initiative Survey (THIS) data set ( N  = 350). Logistic regressions assessed suicidal ideation and attempts. Linear regression assessed the number of suicide attempts. Age was a covariate in all analyses. Social support from family ( B  = -.419, SE = .119, p < .001) was negatively associated with suicidal ideation and was not associated with an attempt history or number of attempts. This finding suggests that increasing social support from family may be an important factor to consider for suicide prevention for gender minority individuals.